Complete Genome Sequence of Herpesvirus anguillae Strain HVA980811 Isolated in Chiayi, Taiwan - Wen, Chiu-Ming (Genome Announc, 2017)
Herpesvirus anguillae (HVA), also known as anguillid herpesvirus 1 (AngHV1), is one of the relevant viruses in wild and cultured anguillid eels. Here, the complete genome sequence of strain HVA980811, isolated in Chiayi, Taiwan, is reported. The genotype of the eel herpesviruses in Taiwan is supposed to be identical to the Japanese AngHV1.